Optimization Of The Learning Process Of Basketball Exercises - U. A. Farmonov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The article raises the problem of optimization of the educational process in physical education classes at the basketball department. Among the students of 1-2 courses aged 17-20 years old, who go in for basketball, priority motives were identified that played a major role in the choice of this sport out of fifteen others presented at the Faculty of Physical Education of BSU. " In the article, we present the main forms of physical education used in the lessons of the educational department of basketball. A comparative analysis of training programs of various orientations during the learning process has been carried out. The main factors of optimization of health-improving physical education classes for students involved in the basketball department have been determined.